Enhancing EFL learners’ engagement in situational language skills through clustered digital materials - Salih, Abdelrahman Abdalla; Omar, Lamis Ismail (Frontiers in Education, 2024)
The tertiary education environment requires students learning English to acquire and develop oral and speaking competencies since they are expected to use communication skills in diverse contexts that serve various purposes. This study investigates the efficacy of clustered digital materials, including TED Talks, digital posters, short films, and newspaper cartoons, in enhancing the English-speaking proficiency of English as a Foreign Language (EFL) learners in an Omani higher learning institution. Employing a mixed-methods approach, the study analyzes data from 37 undergraduate EFL students in digital material-aided situational English classes using statistical tests and qualitative descriptions. Data were collected from participants’ questionnaire responses, semi-structured interviews, and teacher notes. The study reveals that participants preferred incorporating digital materials that required high metacognitive skills and enhanced critical thinking as confirmed by a paired-sample t-test (p < 0.05). Results also demonstrate that participants rated posters as the most desirable digital material, improving speaking and motivating interaction. The findings of the study have important implications for teachers to adopt unconventional pedagogic strategies for coaching, scaffolding, and supporting students while implementing digital materials in conversation classes. This result implies that clustering digital materials in planning pedagogic situational English activities provides language learners with diverse opportunities to collaboratively practice speaking and improve oral and communication competencies.